The need for teachers in the Brussels Region by 2020 - Benjamin Wayens; Bernard Delvaux; Pierre Marissal; Sofie Vermeulen; Benoit Quittelier; Rudi Janssens (Brussels Studies)
In 2019-2020, the Brussels Capital Region will be home to some 24 000 more students than there were in 2013-2014, in preschool, primary and secondary education. This growth generates additional needs in infrastructure, but also in teachers. An interuniversity research team from the Université Libre de Bruxelles, the Vrije Universiteit Brussel, the Université Saint-Louis and the Université catholique de Louvain have analysed the data available so as to have a clearer view of the Brussels perspective. The IBSA/BISA Cahier No 5, summarised in a Brussels Studies Fact Sheet, lays out their estimates of the number of teachers needed in 2019-2020.